Assessment of Occupational Stress on Health Workers in Maternal and Infant Hospitals - Kusumaningtiar, Devi Angeliana; Nuraini, Siti (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Background: Stress is a distortion of the body and mind caused by changes and demands of life. During the Covid 19 pandemic it was shown that the highest levels of stress occurred in health workers, nurses and teachers. Excessive amounts of stress can have harmful effects on the body, mind and psychology. The purpose of this study was to determine the description of the occurrence of work stress on health workers in the inpatient room at Hospital. Methods: The study used a cross sectional design, with a sample of 42 health workers. The sampling technique uses total side method with univariate data analysis. Results: Results with the highest proportion were health workers who experienced work stress as many as 24 respondents (57.1%) which were more dominantly influenced by factors of high workload variation of 31 respondents (73.8%). Conclusions: The hospital is expected to be more aware of the workload and working hours of health workers in order to minimize the risk of work stress.